A study on determinants of islamic saving deposit in Malaysian banking system / Nurul Nisa Kulop Alang - Kulop Alang, Nurul Nisa (2010)
This study is measuring the determinants of Islamic savings deposit in Islamic banking system within 5 years period beginning from 2005 until 2009. Data analysis for this study was done through Statistical Package for Social Science (SPSS) Program in order to analyze and interpret the findings. The main indicator towards measuring the determinants of Islamic savings deposit in Islamic banking system is using the regression analysis. The regression analysis is comprises of 1) Coefficient of determination (R2), 2) F-Statistic, 3) Coefficients, 4) T-Statistic and 5) Durbin- Watson. The results of the study show the determinants of savings deposit in Islamic banking system are different which the money supplies has a significant relationship and has a positive relationship with the balance in Islamic savings account. This proves by the results from the SPSS program used. Overall, the researcher can consider that most of the result gathered in this study is significant.